1885 R.I. Pub. Laws 271, ch. 524, § 1 - (:unkn) unknown (General Publisher, 1885)
Regulated deliveries of gunpowder or other explosive material not marked with a description of contents. Punishable by a fine of not more than ten thousand dollars or not more than five years imprisonment.
--
Keywords: GUN POWDER TRANSPORTATION